Penerapan Sistem Piranti Lunak Personal Finance Berbasis Android untuk Peningkatkan Kualitas Ekonomi Individu - Awaludin, Muryan (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2016)
With a population that is almost dominated by middle-class society economy, it is important for every individual to begin drafting the future as early as possible. The first step that must be done is to adjust costs and increase revenue. On this issue, technology and information can take a role in providing convenience for human needs. With the existence of an application that provides information about the financial arrangements, it is expected that application can be of financial assistance in order to improve people's lifestyles. To the authors conducted a descriptive study related to these problems and their solutions. Research conducted aims to design and implement systems Personal Finance applications using android base. Research Personal Finance app is intended to generate an application program that can simplify the financial arrangements related to budgeting, record keeping money in and out so it can be a personal financial condition in a report which is also the output of the application. Selection android as the application base is so that applications can be more mobile as the rapid use of smartphones, especially smartphone with android operating system